Dynamic Characteristic Analysis of Locomotive Traction Gear based on Simpack - Yuyu Sun; Ye Zhu; Tianmin Guan; Linlin Chai (Jixie chuandong)
In order to analyze the dynamic characteristics of locomotive traction gear transmission system under different operating conditions，taking a certain type of locomotive traction gearbox as the research object，through the Simpack multi-body dynamics software，the time-varying meshing stiffness，damping，friction and other internal excitations of the gear meshing transmission process are considered to establish a traction gear pair dynamics model. Under the two typical working conditions of low speed and high speed，the dynamic characteristics of the driven gear are compared and the amplitude-frequency characteristic curve of the angular acceleration of the torsional vibration of the driven gear is obtained by Fourier transform （FFT）. The accuracy of the dynamics model of the traction gear pair is verified through the above studies，which provides a theoretical basis for the structural optimization design of the gearbox model and the study of the tooth modification of the traction gear.